2023
DOI: 10.1002/ijgo.15222
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal erbium laser treatment for stress urinary incontinence: A multicenter randomized sham‐controlled clinical trial

Barry A. O'Reilly,
Volker Viereck,
Christian Phillips
et al.

Abstract: ObjectiveTo evaluate the efficacy and safety of non‐ablative vaginal Er:YAG laser device in stress urinary incontinence (SUI) treatment.MethodsWe conducted a multicenter blinded randomized sham‐controlled trial in which women with urodynamic SUI were randomization to active arm using Er:YAG laser therapy, and sham arm using sham handpiece. Patients received two treatments 1 month apart. The primary outcomes measure was 1 h pad weight test measured at 6 months. Secondary outcomes were durability of treatment su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…Both VEL and UEL were well tolerated in our study, with no reported complaints from the patients, such as burning during urination or dysuria. Furthermore, there were no observed indications of a risk of urethral stricture associated with laser therapy, which is consistent with previous research [8][9][10][11][12][13][14]19,20].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Both VEL and UEL were well tolerated in our study, with no reported complaints from the patients, such as burning during urination or dysuria. Furthermore, there were no observed indications of a risk of urethral stricture associated with laser therapy, which is consistent with previous research [8][9][10][11][12][13][14]19,20].…”
Section: Discussionsupporting
confidence: 91%
“…Our selection consisted of the non-ablative erbium:yttrium-aluminum-garnet (Er:YAG) SMOOTH® laser, accompanied by a laser tailored for the vagina (vaginal erbium laser (VEL)) and the urethra (urethra erbium laser (UEL)). Previous reports showed that a combination of VEL and UEL improved severe SUI [8][9][10][11][12][13][14]. VEL itself is very 1 2 safe, with few side effects observed [12,14].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Given modern ethical standards, this limitation becomes more complex when considering the difficulty of conducting randomized controlled trials (RCTs) that compare highly invasive procedures with less invasive alternatives given modern ethical standards. Recent studies reporting promising results for VEL suggest that it is a viable and minimally invasive treatment option 14 , 54 . However, the long-term efficacy and safety of this treatment need to be established through further high-quality longitudinal studies.…”
Section: Discussionmentioning
confidence: 99%
“…A common treatment is mid-urethral sling (MUS) procedures using polypropylene mesh, but this method can lead to postoperative pain, foreign body reactions, inflammation, and even the emergence or worsening of Urgency Urinary Incontinence (UUI) 11 13 . Given these issues, Vaginal Erbium Laser (VEL) therapy has gained attention as a non-ablation alternative 14 18 . However, owing to the lack of sufficient data, choosing between MUS and VEL remains challenging.…”
Section: Introductionmentioning
confidence: 99%